Hur dör djur? - Åkesson, Lynn (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2005)
When mourning pets, customs and rituals are in many ways similar to what is used for humans. Graves are decorated with symbols such as crosses, stones with inscriptions, flowers, and candles. On the internet, special web-pages are designed, devoted to the mourning of loved animals. Quite new in a Swedish context are announcements in daily and weekly press, where the obituary notices are designed just the same as for deceased persons. For owners that can not stand the thought of death as the final departure for the loved pet, cloning is an (expensive) alternative. In a Christian context, the borderland between man and beast is absolute, and should not be crossed even by death. This ideological construction does not seem to hold truth for all persons, and the borderline is trespassed by secretly placing the ashes or the whole cadaver of an animal in the coffin containing the remains of the dead owner. Everybody does not approve of customs that equal man and beast, however. Some people think of it as inadequate or silly, some take offence when announcements for dead dogs comes to close to the announcements of deceased relatives. But whether one likes it or not, the market for pets, dead or alive is an expanding and lucrative one.